Adsorption Capacities of Activated Carbons Derived from Rice Straw and Water Hyacinth in the Removal of Organic Pollutants from Water - Wafaa E. Rashwan; Badie S. Girgis (Adsorption Science & Technology)
Two activated carbons were prepared from unconventional raw materials, i.e. rice straw (RS) and water hyacinth (WH), using the same activation scheme, i.e. impregnation with 50 vol% H 3 PO 4 followed by pyrolysis at 500°C. The porosity characteristics of the samples were determined via nitrogen adsorption studies at −196°C from which the various parameters were evaluated. WH carbon showed a more developed porosity relative to RS, although both carbons were apparently of low quality. The capacities of both samples towards the removal from aqueous solution of five organic sorbates were tested. These were phenol (P), p- nitrophenol (PNP), p- nitroaniline (PNA), Methylene Blue (MB) and Congo Red (CR). The adsorption of the two dyes (MB and CR) was a function of the pore dimensions, whereas phenol uptake was greatly reduced because of the acidic oxygen functional groups on the carbon surface. The amount of PNP taken up corresponded exactly with the specific surface area as estimated from nitrogen isotherm measurements. The surface abundances (as μmol/m 2 ) of PNP, P and PNA were found to be independent of the porosity characteristics of the active carbon and followed the general sequence PNP > P > PNA > MB > CR. The observed removal capacities were comparable to that of a commercial carbon produced by Prolabo whose porosity was much more developed.